TRANSFORMATIONAL REHABILITATION: COMMUNITY-BASED INTERVENTION TO END THE DRUG MENACE - Mazo, Generoso N. (International Journal of Research -GRANTHAALAYAH, 2017)
Eradication of the drug menace is the centerpiece program of the Duterte administration. The President claims there are more than 4 million drug users in the country. The police, used the “tok tok-hangyo” or “knock and appeal” approach, to encourage drug users, pushers and others involved to surrender and stop their illegal activities. The nationwide response was overwhelming as 1,176,523, pushers and users submitted voluntarily to authorities. In Tanauan, Leyte, 396 persons, and still increasing, surrendered. Without a national blueprint on how to deal with this problem, Local Governments are left to craft their own programs to help their constituents. The Transformational Rehabilitation Plan Community-Based Approach to Drug Prevention and Moral Recovery Program, a 3-Phases modular approach was implemented with a general objective to enable the participant to understand the process of healing and recovery from their old lifestyles and embrace the new life for the future.